Gene expression of cumulus cells in women with poor ovarian response after dehydroepiandrosterone supplementation - Kuan-Hao Tsui; Li-Te Lin; Huann-Cheng Horng; Renin Chang; Ben-Shian Huang; Jiin-Tsuey Cheng; Peng-Hui Wang (Elsevier, 2014)
Objective: Our previous study showed the potential benefits of dehydroepiandrosterone (DHEA) supplementation in women with a poor ovarian response (POR). Because the connection between cumulus cells (CCs) and oocytes is a key step for oocyte maturation, we supposed that altered gene expression of CCs in women with POR after DHEA supplementation might favor oocyte maturation. Materials and methods: Women with POR treated with flexible daily gonadotropin-releasing hormone antagonist in vitro fertilization (IVF) cycles at The Reproductive Center in Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan between January 2013 and October 2013 were enrolled for this prospective study. CCs were isolated during IVF before and after DHEA (CPH-Formulation, Oakdale, CA, USA) supplementation. Nine genes of isolated CCs, including hyaluronan synthase (HAS2), versican (VCAN), thrombospondin 1 (THBS1), runt-related transcription factor 2 (RUNX2), chromobox homolog 3 (CBX3), tripartite motif-containing 28 (TRIM28), B-cell lymphoma 2 (BCL2), BCL2-associated X protein (BAX), and ankyrin repeat domain 57 (ANKRD57), were compared. Results: There was a significant difference in the expression of genes in women with POR before and after DHEA supplementation (all p < 0.05). All genes related to extracellular matrix (ECM) formation, including HAS2, VCAN, and THBS1, were upregulated. By contrast, all genes involving cell development, differentiation, and apoptosis regulation were downregulated. Unknown function gene ANKRD57 was also downregulated after DHEA supplementation. Although expressions of both BCL2 and BAX were decreased in women with POR after DHEA supplementation compared to those before treatment, the ratio of BCL2 and BAX was significantly increased in women with POR after DHEA supplementation, suggesting that DHEA supplementation might activate the antiapoptosis process of CCs, which might be beneficial to the improvement of ovarian function in women with POR. Conclusion: The study showed that DHEA therapy positively affected the gene expression of CCs in women with POR, and provided evidence to support the positive effect of DHEA supplementation on women with POR.